Gender differences in internet gaming among university students: a discriminant analysis - Gisbert-Pérez, Júlia; Martí-Vilar, Manuel; Merino-Soto, Cesar; Chans, Guillermo M.; Badenes-Ribera, Laura (Frontiers in Psychology, 2024)
Research on gaming and gaming habits has predominantly focused on younger populations, particularly males. The main objective of this study was to analyze genderbased differences in gamer profiles, considering variables related to gaming habits and the gaming community. A total of 180 Spanish university students currently engaged in video gaming (M = 21.51 years, SD = 3.09, 57.4% male) participated in the study by completing an online questionnaire addressing gaming characteristics such as the age of onset, gaming hours, motives of gaming, and perceived toxicity in the video gaming community. The results revealed statistically significant gender differences in the age of gaming initiation, weekly gaming hours, community toxicity, and several gaming motivations, including customization, cognitive challenge, violent gratification, and social interaction. Linear discriminant analysis identified that higher scores in the age of initiation and customization, along with lower scores in violent gratification and community toxicity, formed the combination of predictor variables that most strongly distinguished between genders. Understanding these gender differences is essential for capturing current gaming trends and addressing the needs of diverse gamers. Finally, the potential clinical implications of these findings are discussed.